Legal Protection for Wives and Children as Indirect Victims of Online Gambling Addiction Through the Integration of Family Law, Criminal Law, and Child Protection in Indonesia - Ade Uli Kurniati Siregar (PT. Hafasy Dwi Nawasena, 2026)
The development of information technology has changed patterns of social interaction, including the emergence of various forms of digital-based crime such as online gambling. This phenomenon not only causes economic losses for perpetrators but also has a serious impact on family resilience. Wives and children often become indirect victims of online gambling addiction through neglect of livelihood, domestic violence, psychological disorders, and disruption of children's rights. This study aims to analyze the forms of legal protection for wives and children as indirect victims of online gambling addiction through an integrative approach between family law, criminal law, and child protection law in Indonesia. The study used normative legal methods with statutory, conceptual, and case-based approaches. The results show that although the Indonesian legal system regulates gambling prohibitions and provides protection for women and children, the implementation of legal protection is still sectoral and therefore unable to provide comprehensive protection for the families of online gambling victims. Therefore, it is necessary to strengthen coordination between law enforcement agencies, women's and children's protection institutions, and develop policies that place the family at the center of legal protection.